Using expert knowledge to support Endangered Species Act decision‐making for data‐deficient species. Issue 5 (16th March 2021) - Fitzgerald, Daniel B.; Smith, David R.; Culver, David C.; Feller, Daniel; Fong, Daniel W.; Hajenga, Jeff; Niemiller, Matthew L.; Nolfi, Daniel C.; Orndorff, Wil D.; Douglas, Barbara; Maloney, Kelly O.; Young, John A.
Abstract: Many questions relevant to conservation decision‐making are characterized by extreme uncertainty due to lack of empirical data and complexity of the underlying ecologic processes, leading to a rapid increase in the use of structured protocols to elicit expert knowledge. Published ecologic applications often employ a modified Delphi method, where experts provide judgments anonymously and mathematical aggregation techniques are used to combine judgments. The Sheffield elicitation framework (SHELF) differs in its behavioral approach to synthesizing individual judgments into a fully specified probability distribution for an unknown quantity. We used the SHELF protocol remotely to assess extinction risk of three subterranean aquatic species that are being considered for listing under the U.S. Endangered Species Act. We provided experts an empirical threat assessment for each known locality over a video conference and recorded judgments on the probability of population persistence over four generations with online submission forms and R‐shiny apps available through the SHELF package. Despite large uncertainty for all populations, there were key differences between species' risk of extirpation based on spatial variation in dominant threats, local land use and management practices, and species' microhabitat. The resulting probability distributions provided decision makers with a full picture of uncertainty that was consistent with the probabilistic nature of risk assessments. Discussion among experts during SHELF's behavioral aggregation stage clearly documented dominant threats (e.g., development, timber harvest, animal agriculture, and cave visitation) and their interactions with local cave geology and species' habitat. Our virtual implementation of the SHELF protocol demonstrated the flexibility of the approach for conservation applications operating on budgets and time lines that can limit in‐person meetings of geographically dispersed experts. Abstract : Article Impact Statement : Remote expert elicitation can facilitate endangered species decision‐making when available data, budgets, and time frames are limiting. Abstract : Uso del Conocimiento Experto para Respaldar la Toma de Decisiones del Acta de Especies en Peligro para Especies con Información Deficiente Resumen: Muchas preguntas relevantes para la toma de decisiones de conservación se caracterizan por una incertidumbre extrema causada por la falta de información empírica y por la complejidad de los procesos ecológicos subyacentes. Esto lleva a un rápido incremento en el uso de protocolos estructurados para obtener conocimiento de los expertos en el tema. Las aplicaciones ecológicas publicadas con frecuencia emplean un método Delphi modificado, en el cual los expertos proporcionan dictámenes anónimamente y luego se usan técnicas de agregación matemática para combinar estos dictámenes. El marco de trabajo de obtención Sheffield (SHELF) difiere en su enfoque conductual para sintetizar los dictámenes individuales en una distribución de probabilidad completamente especificada para una cantidad desconocida. Usamos el protocolo SHELF remotamente para evaluar el riesgo de extinción de tres especies acuáticas subterráneas que están siendo consideradas para ser incluidas en el Acta de Especies en Peligro de los E.U.A. Les proporcionamos a los expertos una evaluación empírica de la amenaza para cada localidad conocida durante una videoconferencia y registramos los dictámenes sobre la probabilidad de la persistencia poblacional durante cuatro generaciones por medio de formularios enviados en línea y las apps R‐shiny disponibles a través del paquete SHELF. A pesar de la gran incertidumbre para todas las poblaciones, hubo diferencias importantes entre el riesgo de extirpación de las especies con base en la variación espacial en las amenazas dominantes, el uso del suelo local y las prácticas de manejo, y el microhábitat de las especies. Las distribuciones resultantes de la probabilidad proporcionaron al órgano decisorio un cuadro completo de la incertidumbre que fue consistente con la naturaleza probabilística de las evaluaciones de riesgo. Las discusiones entre los expertos durante la fase de agregación conductual de SHELF documentaron claramente las amenazas dominantes (p. ej.: desarrollo, extracción de madera, agricultura animal y visitas a las cuevas) y sus interacciones con la geología de las cuevas locales y el hábitat de la especie. Nuestra implementación virtual del protocolo SHELF demostró la flexibilidad del enfoque para las aplicaciones de la conservación que operan con presupuestos y líneas de tiempo que pueden limitar las reuniones en persona de expertos dispersados geográficamente. 【摘要】: 由于经验数据的缺乏和潜在生态过程的复杂性, 许多与保护决策相关的问题具有极端不确定性, 这导致使用结构化研究方案来获得专家知识的实践迅速增加。在已有生态学应用中, 研究者通常采用一种改进的德尔菲法, 即用数学整合方法来综合专家匿名提供的判断。而谢菲尔德启发式框架 (SHELF) 的不同之处在于, 它的行为方法是将个人判断整合为一个未知量完全指定的概率分布。我们利用 SHELF 方法远程评估了正被考虑列入《美国濒危物种法案》的 3 种地下水生物种的灭绝风险。我们通过视频会议向专家提供了对每个已知分布点威胁的经验评估, 并通过在线提交表格和 SHELF 包的 R‐shiny 应用程序记录了专家对这些物种 4 代以上续存概率的判断。虽然所有种群都存在很大的不确定性, 但由于其主要威胁、当地土地利用及管理措施和物种微生境的空间差异, 物种灭绝风险也存在明显差异。由此得出的概率分布为决策者提供了不确定性的整体情况, 这与风险评估的概率特性相一致。专家们在 SHELF 框架整合阶段的讨论清楚地记录了主要威胁 (如开发、木材采伐、畜牧业和探洞) 以及它们与当地洞穴地质和物种栖息地的相互作用。我们对 SHELF 框架的虚拟实现展示了保护应用在预算和时间上的灵活性, 从而可以减少分散在各地的专家的现场会议。 【翻译: 胡怡思; 审校: 聂永刚】